Meridional Contrasts in Productivity Changes Driven by the Opening of Drake Passage - Ladant, Jean-Baptiste; Donnadieu, Yannick; Bopp, Laurent; Lear, Caroline; Wilson, Paul (Paleoceanography and Paleoclimatology, 2018)
International audience Changes in atmospheric pCO(2) are widely suggested to have played a major role in both the long-term deterioration of Cenozoic climate and many superimposed rapid climate perturbations such as the pivotal Eocene-Oligocene transition. Changes in marine productivity affecting the biological oceanic carbon pump represent one possible cause of past CO2 variability. Here we explore the relationship between ocean gateway change and marine biogeochemistry. Specifically, we use a fully coupled atmosphere-ocean-biogeochemical model (IPSL-CM5A) to examine global ocean paleoproductivity changes in response to the opening of Drake Passage. In our simulations, we find that Drake Passage opening yields a spatially uniform decrease in primary productivity in the low-latitude oceans while the high-latitude response is more spatially heterogeneous. Mechanistically, the low-latitude productivity decrease is a consequence of a fundamental reorganization of ocean circulation when Drake Passage opens driven by the isolation of the Southern Ocean from low-latitude water masses. Nutrient depletion in the low latitudes is driven by a marked decrease in the intensity of deep convection in the Southern Ocean, which drives the accumulation of nutrients at depth and their depletion in the intermediate and upper ocean, especially away from sites of subduction. In the high latitudes, the onset of the Antarctic Circumpolar Current in the model exerts a strong control both on nutrient availability and on regions of deep-water formation. The qualitative agreement between geographically diverse long-term paleoproductivity records and the simulated variations suggests that Drake Passage opening may contribute to the long-term paleoproductivity signal.